2005
DOI: 10.1093/jn/135.6.1557s
|View full text |Cite
|
Sign up to set email alerts
|

Branched-Chain Amino Acid Metabolism: Implications for Establishing Safe Intakes

Abstract: There are several features of the metabolism of the indispensable BCAAs that set them apart from other indispensable amino acids. BCAA catabolism involves 2 initial enzymatic steps that are common to all 3 BCAAs; therefore, the dietary intake of an individual BCAA impacts on the catabolism of all 3. The first step is reversible transamination followed by irreversible oxidative decarboxylation of the branched-chain alpha-keto acid transamination products, the branched chain alpha-keto acids (BCKAs). The BCAA ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
187
1
8

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 221 publications
(200 citation statements)
references
References 63 publications
4
187
1
8
Order By: Relevance
“…Desse modo, a transaminação dos ACR fornece mecanismos para transferir o nitrogênio dos ACR de acordo com a necessidade do tecido por glutamato e outros aminoácidos não-essenciais. Além disso, cabe ressaltar que as isoenzimas ATACR em mamíferos são muitos específicas para ACR e glutamato, sendo a preferência de substratos a seguinte: isoleucina > valina >> glutamato (Cynober, Harris, 2006;Harris et al, 2005;Hutson, Sweatt, Lanoue, 2005;Harris, Joshi, Jeoung, 2004).…”
Section: Metabolismo Dos Aminoácidos De Cadeia Ramificadaunclassified
See 1 more Smart Citation
“…Desse modo, a transaminação dos ACR fornece mecanismos para transferir o nitrogênio dos ACR de acordo com a necessidade do tecido por glutamato e outros aminoácidos não-essenciais. Além disso, cabe ressaltar que as isoenzimas ATACR em mamíferos são muitos específicas para ACR e glutamato, sendo a preferência de substratos a seguinte: isoleucina > valina >> glutamato (Cynober, Harris, 2006;Harris et al, 2005;Hutson, Sweatt, Lanoue, 2005;Harris, Joshi, Jeoung, 2004).…”
Section: Metabolismo Dos Aminoácidos De Cadeia Ramificadaunclassified
“…Desse modo, a transaminação dos ACR fornece mecanismos para transferir o nitrogênio dos ACR de acordo com a necessidade do tecido por glutamato e outros aminoácidos não-essenciais. Além disso, cabe ressaltar que as isoenzimas ATACR em mamíferos são muitos específicas para ACR e glutamato, sendo a preferência de substratos a seguinte: isoleucina > valina >> glutamato (Cynober, Harris, 2006;Harris et al, 2005;Hutson, Sweatt, Lanoue, 2005;Harris, Joshi, Jeoung, 2004).Posteriormente à reação catalisada pela enzima ATACR e à conseqüente formação dos cetoácidos de cadeia ramificada, esses podem sofrer descarboxilação oxidativa mediada pelo complexo enzimático DCCR -presente na superfície interna da membrana interna mitocondrial. Por meio da reação catalisada pelo complexo DCCR, os cetoácidos de cadeia ramificada KIC, KMV e KIV são convertidos em isovaleril-CoA, 3-metilbutiril-CoA e isobutiril-CoA, respectivamente.…”
unclassified
“…The forward nitrogen transfer is favored by oxidation of the BCKA products by BCKDC. Net nitrogen transfer from BCAAs to glutamate occurs when the carbon skeleton of the BCAA is irreversibly lost via the BCKDC step (oxidation) (11).…”
mentioning
confidence: 99%
“…The branched-chain amino acids (BCAAs), leucine, isoleucine, and valine, cannot be synthesized endogenously in mammals, 1) and are therefore classified as nutritionally essential or indispensable amino acids. Mounting evidence indicates that BCAAs have various physiological and metabolic functions.…”
mentioning
confidence: 99%
“…Mounting evidence indicates that BCAAs have various physiological and metabolic functions. 1,2) It has been reported that intake of individual or combined BCAAs 3,4) or ingestion of proteins 5) affects the plasma amino acid profile. In addition of acute changes in the plasma amino acid profiles associated with ingestion of amino acids and proteins, the plasma amino acid profile has been the focus of increasing attention because of its prospective application in the diagnosis and assessment of disease and pathophysiological states.…”
mentioning
confidence: 99%